Asuhan Keperawatan Komunitas Pada Ny.R Dengan Gangguan Sistem Muskuloskeletal : Gout Arthritis Di Desa Tonjong Dukuh Kauman Selatan RT02/RW04 Kecamatan Tonjong Kabupaten Brebes - Salsabiila Roikhatul Janah; Siti Fatimah (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2026)
Background: Community nursing is a specialty field that combines nursing science skills, public health sciences, and social assistance in addressing individual and family health problems, including non-communicable diseases such as gout arthritis. Gout arthritis is a metabolic disease characterized by pain and joint inflammation due to the accumulation of purine crystals (hyperuricemia). The WHO reports a prevalence of gout arthritis reaching 3.74% globally, while in Indonesia the prevalence reaches 11.9% based on health worker diagnosis. In Brebes Regency, the prevalence reaches 13.67%, with 3,078 sufferers out of 22,550 productive-age population. Objective: To provide comprehensive community nursing care to Ny. R with musculoskeletal system disorder: gout arthritis in Tonjong Village, Tonjong District, Brebes Regency. Method: This study uses a case study approach with data collection through interview, observation, physical examination, and documentation study conducted on December 2628, 2025. Results: Assessment findings showed that Ny. R, a 60-year-old woman, had a history of gout arthritis for 3 months with uric acid levels of 9.6 mg/dL, complaining of pain and aching in the left foot with pain scale 3. Two nursing diagnoses were established: acute pain and knowledge deficit. Nursing interventions included pain management, uric acid level monitoring, lemongrass stem decoction foot soak complementary therapy, and health education using leaflets. After 2 days of implementation, uric acid levels decreased to 8.2 mg/dL and pain scale decreased to 2. Conclusion: Community nursing care through complementary therapy (lemongrass stem decoction foot soak) and health education effectively reduced pain and improved knowledge about gout arthritis in Ny. R.